Study on proportion optimization of coal-based solid wastes filling materials - Tang Yuesong; Zhang Lingfei; LÜ Huayong (矿业科学学报, 2019)
The aim of this study is to prepare a low cost and high strength filling material.Coal gangue is aggregate.Fly ash,desulfurization gypsum and silicium-calcium slag are cementing materials.The uniaxial compressive strength,slump and slump flow of the specimen were measured to investigate the mechanical properties and the influence of each component.The result shows that desulphurization gypsum content and silicium-calcium slag have a strong gelation effect in certain amount range.With the increase of content of fly ash,the initial strength of filling material increases slowly.The content of fly ash should be controlled less than 6.67%.The mixing of fly ash and silicium-calcium slag could activate cementious properties of silicium-calcium slag performance.The optimum mass ratios of coal gangue,fly ash,desulfurization gypsum,silicium-calcium slag and cement are 70:6:3:12.5:8.5.The conclusion is verified by response surface method,and the experimental results are consistent with the prediction.